Overcoming Drought Problems in Selengen Village, North Lombok through Simple Technology of Fog Harvesting and Seawater Distillation - Syauqi, Shofiyurrahman; Uswatul Ulya; Gina Sonia; Mochammad Restu Julian; Maiser Syaputra (Universitas Mataram, 2025)
Drought is a serious problem faced by the people of Selengen Village, North Lombok, especially during the dry season. Limited clean water sources hamper agricultural activities and domestic needs. To overcome this water crisis, two simple technologies were applied: fog harvesting and seawater distillation. The fog harvesting technology utilizes air humidity to produce clean water, while seawater distillation uses solar energy to convert saltwater into potable water. A participatory approach was applied through counseling, training, and mentoring for the community and students of SMKN 1 Kayangan. Results show that both technologies have potential as alternative solutions to drought, although their effectiveness is affected by weather conditions. Further education and mentoring are needed to improve the sustainability of the application of these technologies.